Morphometric Dimensions of Superior Orbital Fissure: A Cross-sectional Study - Amarbir Kaur; Poonam Delmotra; Kuldeep Singh; JS Kullar; Ravi Kant Sharma (International Journal of Anatomy Radiology and Surgery, 2022)
Introduction: Superior Orbital Fissure (SOF) is located between the roof and lateral wall of the orbit. SOF exhibits complex anatomy because of abundant neurovascular structures running through or near it and it connects the orbit with cranial cavity. Variant anatomy, in terms of morphology of SOF is well documented in literature, but data regarding morphometrical study of SOF is limited.